Evaluating Factors that Impact Sme’s Npd Success in South African Retail Industry - Devapriya, Kailash Nath Sharma; Lotriet, Ronnie (Nurture, 2025)
This study examines the determinants of new product development (NPD) performance and retailer engagement among South African small and medium-sized enterprises (SMEs). It investigates how strategic orientation, NPD research, team collaboration, and retailer–supplier relationship quality shape innovation outcomes in a resource-constrained retail environment. A positivist quantitative research design was adopted, and data were collected from 74 SME owner–managers using a structured online questionnaire. Descriptive, correlation, and regression analyses were conducted in SPSS (v28.0). Findings show that NPD research is the only statistically significant predictor of retailer engagement (β = 0.61, p < 0.05). Structured customer validation, market testing, and evidence-based learning therefore play a decisive role in improving SMEs’ credibility with retail buyers. Although strategic alignment and cross-functional collaboration show positive associations with NPD outcomes, neither exerts a significant effect on retailer accessibility. The results highlight a persistent “intent–execution gap” in SMEs: while strategic awareness and innovation culture are strong, weak institutionalisation of research and collaboration limits NPD effectiveness. Retailer–supplier relationships remain characterised by information asymmetry, limited feedback, and procedural opacity, reflecting structural power imbalances in South Africa’s concentrated grocery sector. Strengthening research-driven NPD routines, shared market intelligence, and transparent supplier-development mechanisms can improve SME access to dominant retail channels. The study contributes to the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT) by demonstrating how research intensity and learning routines enhance SMEs’ market legitimacy within asymmetric value chains.